Flow simulation of GO Nanofluid inside semi porous channel - Azimi, Mohammadreza; Azimi, Alireza (My University, 2014)
In this study, the analytical solution of the graphene oxide-water nanofluid inside semi permeable channel has been presented. The Reconstruction of Variational Iteration Method (RVIM) has been used to compute an approximate solution of the nonlinear differential equation. Comparisons are made between the numerical solution and the results of the RVIM. The effects of different parameters, especially the effect of the solid volume fraction of graphene oxide nanoparticle on velocity are investigated and shown graphically. The dynamic viscosity and the effective thermal conductivity of the nanofluid have been approximated by the Brinkman and Maxwell-Garnetts models respectively
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Graphene oxide; Nanofluid; Nanofluid; Flow simulation; RVIM